Debilidades en los programas que forman docentes en educación matemática: percepción de los actores (ING) - Chaves Esquivel, Edwin (2003)
A question arises about the quality of teachers training based on criticisms concerning poor performance in High School mathematics. This paper attempts to determine the weaknesses of academic programs for teacher training in Mathematics Education in Costa Rica. To achieve this, we consider the opinions of current students in these programs and of teachers who graduated from them. The information gathered from a self-administered survey of the opinions of 171 students and 172 teachers was analyzed. Both groups agree that the main strength of these programs is mathematical training and logical thinking. However there was some unhappiness over a series of weaknesses that greatly affect classroom performance. The main criticism arises from the existing divorce between courses in mathematics and pedagogy. In their opinion there is no relation among these courses to let them promote teaching methodologies for specific areas of mathematics. A strong lack of historical, philosophical and methodological studies has been perceived within their academic training. Also they point to the need of practical applications of different mathematical concepts. The pollsters also consider that there is no strategy development to let them participate in serious research processes in Mathematics Education. Finally, they consider that they are not well trained in the use of modern technological resources. These opinions provide an important reference to evaluate the work of the universities in these training processes, and the wisdom of training future specialist in this discipline.